Sexual offending - Sullivan, Danny H. (Seminars in forensic psychiatry, 2024)
Sexual offending is astonishingly prevalent and is associated with significant mental health and psychosocial consequences for victims. It is also the basis of a range of severe criminal justice sanctions, which in various jurisdictions can include indeterminate sentences as well as post-sentence restrictions. Of all forms of offending, it is sexual offending which is most stigmatised and despised, and this may lead to vigilantism and persecution of offenders or those perceived to be offenders.